Small boat navigating the Snake River, Nome, Alaska, September 29, 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Snake River, Nome Sept 29" Original image in Hegg Album 5, page 38. Original photograph by Eric A. Hegg 1214; copied by Webster and Stevens 379.A.